Construction of Tissue‐Level Cancer‐Vascular Model with High‐Precision Position Control via In Situ 3D Cell Printing. Issue 7 (28th April 2021) - Kim, Byoung Soo; Cho, Won‐Woo; Gao, Ge; Ahn, Minjun; Kim, Jongmin; Cho, Dong‐Woo
Abstract: During tumor progression, the size and location of the tumor are important factors closely associated with the metastatic potential of the cancer as they largely govern tumor hypoxia and angiogenesis. However, despite the achievements of previous studies, these critical factors are poorly studied, mainly due to the lack of a flexible technique that can readily control 3D tumor mimicking constructs and their spatial relations with vasculature. Here, a novel tissue‐level platform consisting of a metastatic cancer unit (MCU) and a perfusable vascular endothelium system (VES) is presented using in situ 3D cell printing. Size‐tunable and position‐controllable 3D cancer spheroids (500–1000 µm) are directly printed within the established bath bioink with a self‐driven perfusable vascular channel. The cancer‐vascular interactions are generated through controlling the distance between MCU and VES to investigate metastasis‐associated changes at adjacent and distal regions. The result shows that MCU in 600 µm diameter includes hypoxia, invasion, and angiogenetic signaling. The further observations demonstrate that the proximity of MCU to VES augments the epithelial‐mesenchymal transition (EMT) in MCU and vascular dysfunction/inflammation in VES, corroborating the positional significance in tumor metastasis. The platform with the precise‐positioning control enables the recapitulation of patient's detailed metastatic progression, opening the chance for precision cancer medicine. Abstract : Here, a novel tissue‐level platform consisting of metastatic cancer units (MCUs) and a perfusable vascular endothelium system (VES) is presented using in situ 3D cell printing. Size‐tunable and position‐controllable 3D cancer spheroids are directly printed within the supporting bath with a perfusable vascular channel. The cancer‐vascular interactions are generated through controlling the distance between MCU and VES.